2017
DOI: 10.1111/andr.12424
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone does not affect agrin cleavage in mobility‐limited older men despite improvement in physical function

Abstract: In a subset of men, sarcopenia and physical dysfunction occur due to destabilization of the neuromuscular junction (NMJ), which is manifested by elevated serum concentrations of C-terminal agrin fragment (CAF). Testosterone administration improves physical function in some studies; however, its effects on serum circulating CAF concentrations remain unknown. Here we evaluate the effects of testosterone administration on circulating CAF levels in mobility-limited men with low testosterone aged 65 or older partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 44 publications
0
24
0
1
Order By: Relevance
“…The randomized controlled trials (RCTs) published since 2010 are summarized in Table 2 [ 50 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Their results varied by target population, type of testosterone formulation, and testosterone dosage.…”
Section: Efficacy Of Testosterone Replacement Therapy For Sarcopeniamentioning
confidence: 99%
See 3 more Smart Citations
“…The randomized controlled trials (RCTs) published since 2010 are summarized in Table 2 [ 50 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Their results varied by target population, type of testosterone formulation, and testosterone dosage.…”
Section: Efficacy Of Testosterone Replacement Therapy For Sarcopeniamentioning
confidence: 99%
“…Their results varied by target population, type of testosterone formulation, and testosterone dosage. Many of the RCTs investigated the effects on muscle of TRT among men with low to normal testosterone levels and 15 of 19 RCTs supported certain merits of TRT on muscle volume [ 50 , 67 , 68 , 69 , 70 , 72 , 73 , 74 , 75 , 76 , 77 , 79 , 80 , 81 , 82 ]. The other four studies, however, failed to demonstrate that TRT contributes to improving muscle mass or strength [ 65 , 66 , 71 , 78 ].…”
Section: Efficacy Of Testosterone Replacement Therapy For Sarcopeniamentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, Gagliano‐Jucá et al 56 observed a raise in CAF concentration over 6 months in frail, old individuals; interestingly, testosterone administration was not able to prevent such raise, despite increasing muscle strength. The authors suggested that this hormone exploits pathways other than a restore in NMJ stability to induce force ameliorations 56 …”
Section: Caf Assessment: Which Conditions and Which Results?mentioning
confidence: 89%